1990
DOI: 10.1038/bjc.1990.152
|View full text |Cite
|
Sign up to set email alerts
|

DNA index, S-phase fraction, histological grade and prognosis in breast cancer

Abstract: Summary DNA index and S-phase fraction (SPF) were Multivariate analysis using the Cox model suggested that, while SPF gave prognostic information independent of tumour size or nodal status, this independent significance was lost when histological grade was included in the analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
30
1
5

Year Published

1992
1992
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(40 citation statements)
references
References 16 publications
4
30
1
5
Order By: Relevance
“…which is in agreement with other studies (Feichter et al, 1988;Kallioniemi et al. 1987: O'Reilly et al. 1990).…”
supporting
confidence: 83%
“…which is in agreement with other studies (Feichter et al, 1988;Kallioniemi et al. 1987: O'Reilly et al. 1990).…”
supporting
confidence: 83%
“…Flow cytometric measurement of DNA content per nucleus provides information both about DNA ploidy status and about proliferative activity as represented by the fraction of cells in the S-phase of the cell cycle, The prognostic value of DNA ploidy has been demonstrated in many studies (6,8,9,20,24,42), as has that of the S-phase fraction (SPF; 13,15,16,22,31,37), though others have failed to confirm the independent prognostic value of these variables (12,21,30). sults.…”
mentioning
confidence: 99%
“…It was impossible to extend the comparison to the whole series because of either insufficient material or technical problems but, in view of our results on the 64 cases and the association between SPF and histological grade already established for our samples (O'Reilly et al, 1990), we considered that the number of cases with results by both methods was sufficient to confirm MIB 1 immunohistochemistry as a good marker of proliferative activity. Others have confirmed this finding and also shown that MIBI is strongly associated with other recognized markers of proliferation, including mitotic count and Ki-67 expression (Lipponen et al, 1992;McCormick et al, 1993;Ellis et al, 1996).…”
Section: Resultsmentioning
confidence: 91%